The The Impact of Science Storming on Students’ Scientific Literacy in Elementary Education - Arif, Almaidah Purnamasari; Nizaar, Muhammad; Haifaturrahmah; Nagy, Emese Kovacsne (Universitas prof. Dr. Moestopo (Beragama), 2026)
This study aims to analyze the effectiveness of the Science Storming learning model in improving science literacy among elementary school students. The study employed a quantitative approach with a quasi-experimental design (nonequivalent control group pretest-posttest). The research subjects consisted of fifth-grade students divided into an experimental group (n=22) and a control group (n=16). The instrument used was a science literacy test covering the ability to understand changes in the state of matter, the relationship between temperature and changes in state, and the interpretation of scientific phenomena. Data analysis utilized descriptive statistics, normality tests, paired-sample t-tests, and independent-sample t-tests. Results showed a pretest mean of 59.69 for the control group and 60.00 for the experimental group, while posttest scores increased to 67.64 (control) and 85.64 (experimental). The paired t-test for the experimental group showed a significant difference (mean difference = −25.636; p < 0.05). These findings indicate that Science Storming is effective in improving science literacy through the exploration of ideas and scientific discussions that foster a deeper and more contextual conceptual understanding.